The CSR practices of Western Australian mining based on innovation ecosystems: Pathways to collaborative innovation and sustainable development - Sun, Jiawei (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the Corporate Social Responsibility (CSR) practices of Western Australian mining companies, focusing on their integration of innovation ecosystems to promote sustainable development. Through case studies of BHP Group, Rio Tinto, FMG, and South32, the research examines how these companies reduce carbon emissions, enhance community development, and foster collaborative innovation. The findings highlight the significant role of innovation ecosystems in enabling these companies to adopt cleaner technologies, improve social outcomes, and maintain a competitive edge in a sustainability-conscious global market. The study also explores the challenges and opportunities faced by mining companies in leveraging collaborative innovation to address complex environmental and social issues. This research contributes to the understanding of CSR in the mining industry and offers practical insights for improving sustainability practices through innovation-driven collaboration.